Chaperonopathies: Spotlight on Hereditary Motor Neuropathies - Lupo, Vincenzo; Aguado, Carmen; Knecht, Erwin; Espinós, Carmen (Frontiers in Molecular Biosciences, 2016)
Distal hereditary motor neuropathies (dHMN) comprise a group of rare hereditary neuromuscular disorders characterized by a peroneal muscular atrophy without sensory symptoms. To date twenty-three genes for dHMN have been reported and four of them encode for chaperones: DNAJB2, which encodes a member of the HSP40/DNAJ co-chaperone family, and HSPB1, HSPB3 and HSPB8, which encode three members of the family of small heat shock proteins. Except for HSPB1, with around thirty different mutations, the remaining three genes comprise a much low number of cases. Thus, only one case has been described caused by an HSPB3 mutation, whereas few DNAJB2 and HSPB8 cases are known, most of them caused by a founder c.352+1G>A mutation in DNAJB2 and by mutations affecting the hot spot K141 residue of the HSPB8 chaperone. This low number of cases makes it difficult to understand the pathomechanism underlying the neuropathy. Chaperones can assemble in multi-chaperone complexes forming an integrative chaperone network in the cell, which plays relevant cellular roles in a variety of processes such as the correct folding of newly synthesized proteins, their escort to their precise cellular locations to form functional proteins and complexes and the response to protein misfolding, including the degradation of proteins that fail to refold properly. Despite of this variety of functions, mutations in some of them lead to diseases with a similar clinical picture, suggesting common pathways. This review gives an overview of the genetics of dHMNs caused by mutations in four genes, DNAJB2, HSPB1, HSPB3 and HSPB8, which encode chaperones and show a common disease mechanism.